PENGARUH PENERAPAN STRATEGI THE FIRING LINE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 SOLOK SELATAN - Putri, Trionita Dwi (Pendidikan Matematika, 2014)
The background of this research is the lack of students comprehension ofmathematical concept and the less of students responsible in learning. Theresearch purpose is to define whether the students comprehension ofmathematical concept by applying "The Firing Line" Strategy better than thestudents comprehension of mathematical concept by applying conventionalstrategy. The research design is experiment. The researcher used RandomTerhadap Subjek. The population of this research was students in eighth gradeSMP Negeri 5 Solok Selatan. The technique used was random sampling. Analysistechnique that was used is t test supported by MINITAB. The result of P valueless than a. Therefore, the hyphotesis accepted. Consequently, it can be concludethat students comprehension of mathematical concept by applying The FiringLine Strategy better than the students comprehension of mathematical concept byapplying conventional strategy.